2014
DOI: 10.1177/1524839913510919
|View full text |Cite
|
Sign up to set email alerts
|

A Needs Assessment of Health Department Employees in Puerto Rico and Florida

Abstract: Public health training centers were established to enhance competencies in skills required to meet 21st-century public health challenges. In 2011, the Puerto Rico-Florida Public Health Training Center conducted surveys to assess the training needs of two populations of public health workers serving Hispanic communities: Florida Department of Health employees and workers at the regional and central offices of the Puerto Rico Department of Health. The two surveys were similar, but not identical in content and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Knowing self-status helped them to feel more responsible and take care of their and others health too. This finding is similar with studies from Botswana, South Africa, and Puerto Rico where similar population groups have depicted the same self-disclosure timing and benefit from it [7,[22][23][24]. When it is said self-disclosure it is important to make it in plan than leaving children to learn about their HIV status incidentally when they visit health care facilities for other medical services or leave them to learn by their own or hearing from somebody else.…”
Section: Discussionsupporting
confidence: 84%
“…Knowing self-status helped them to feel more responsible and take care of their and others health too. This finding is similar with studies from Botswana, South Africa, and Puerto Rico where similar population groups have depicted the same self-disclosure timing and benefit from it [7,[22][23][24]. When it is said self-disclosure it is important to make it in plan than leaving children to learn about their HIV status incidentally when they visit health care facilities for other medical services or leave them to learn by their own or hearing from somebody else.…”
Section: Discussionsupporting
confidence: 84%
“…Training needs assessments typically provide the information necessary to identify knowledge and skill gaps across the workforce targeted by the assessment (Frass et al, 2014; Goldstein & Ford, 2002). Conducting regular needs assessments is an integral step to ensuring that R-IV PHTC trainings are relevant and meet the evolving needs and preferences of public health professionals throughout R-IV (Capriles-Quirós et al, 2014). To this end, and because of the complex nature of R-IV and the challenges mentioned above, a mixed methods approach was employed.…”
Section: Identifying and Addressing Training Needs In A Diverse Regionmentioning
confidence: 99%
“…The focus of their article is a collaborative methodology that yielded an impressive return rate. Capriles-Quirós et al (2014) describe the needs assessment conducted of public health workers serving two very different Hispanic communities. Using survey instruments adapted to the settings, they found that both groups of professionals ranked the assessed competencies in the lowto mid-range and preferred hands-on and face-to-face training to distance learning.…”
Section: > > Overview Of This Special Issuementioning
confidence: 99%